Design of high entropy alloys for hydrogen storage: study of the Mg-V-Al-Cr-Ni, Mg-Al-Ti-Mn-Nb and Ti-V-Nb-Cr systems - Strozi, Renato Belli (2021)
The advent of high entropy alloys (HEA) has brought new opportunities and challenges to metallurgy. Due to extensive compositional field of HEAs, the possibility of controlling properties in a composition-driven approach becomes evident. However, this vast compositional field demands enormous efforts to select promising alloys for a given application. Up to now, an accurate model to effectively designing HEAs for hydrogen storage is still lacking. Thus, this thesis is dedicated to investigating the effects of the chemical composition on the structural and hydrogen storage properties of body-centered cubic (BCC) HEAs for hydrogen storage applications. Firstly, a set of lightweight HEAs of the Mg-V-Al-Cr-Ni system was produced by high-energy ball milling (HEBM). The experimental results indicate that a single-phase solid solution was only obtained for the equiatomic composition. The investigated alloys exhibited poor hydrogen storage properties. This behavior brought to light the importance of balancing hydride- and non-hydride-forming elements to tune the alloy’s hydrogen affinity, specially considering the mean enthalpy of hydrogen solution of the alloying elements. In a second step, a semi-empirical design method was employed to screen a single-phase BCC alloy with high hydrogen affinity from the Mg-Al-Ti-Mn-Nb system. Through the calculation of four composition-dependent parameters (φ, VEC, mean enthalpy of hydrogen solution and mean mean enthalpy ), the Mg12Al11Ti33Mn11Nb33 alloy was designed. When produced by HEBM, this alloy exhibited a single-phase BCC structure and interesting hydrogen storage properties, indicating that the design approach can be successfully applied to find interesting compositional regions for a multicomponent system, decreasing the number of experiments needed to find alloys with appropriate properties for hydrogen storage. In the third part of this study, the effects of adding a non-hydride-forming element in a multicomponent system composed only of hydride-forming elements was investigated. The CALPHAD method was applied to find a suitable alloy system. The (TiVNb)100-xCrx alloy system was selected, with x = 15, 25, and 35 at.%. In this range of composition, the CALPHAD method indicates the formation of single-phase BCC during solidification for the three alloys, which was confirmed experimentally. The hydrogen storage performance was evaluated, and it was verified that increasing the Cr/(TiVNb) ratio leads to significant increase in the equilibrium plateau pressure of the (TiVNb)100-xCrx alloys, without significant loss of maximum hydrogen storage capacity. It was demonstrated that the proportion of a non-hydride forming element can be used to tune the hydrogen storage properties of the HEAs.